2021
DOI: 10.1371/journal.pone.0256319
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of a wild and a cultivated varieties of Capsicum annuum over fruit development and ripening

Abstract: Chili pepper (Capsicum annuum) is one of the most important crops worldwide. Its fruits contain metabolites produced over the maturation process like capsaicinoids and carotenoids. This metabolic process produces internal changes in flavor, color, texture, and aroma in fruits to make them more attractive for seed dispersal organisms. The chiltepin (C. annuum L. var. glabriusculum) is a wild variety of the C. annuum L. species that is considered a source of genetic resources that could be used to improve the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 101 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…These results might suggest that activation of ethylene signaling and the subsequent alteration of ethylene sensitivity could be conserved in non-climacteric fruits [18,19]. In contrast, upregulation of ethylene receptor-like protein (ETR), a key regulator of the ethylene transcription pathway, was detected in a transcriptomic analysis of C. frutescens and C. annuum performed at different stages of ripening, suggesting that at least some species of chili pepper exhibit climacteric behavior [20,25].…”
Section: Chili Pepper Ripening Regulation Processmentioning
confidence: 98%
See 3 more Smart Citations
“…These results might suggest that activation of ethylene signaling and the subsequent alteration of ethylene sensitivity could be conserved in non-climacteric fruits [18,19]. In contrast, upregulation of ethylene receptor-like protein (ETR), a key regulator of the ethylene transcription pathway, was detected in a transcriptomic analysis of C. frutescens and C. annuum performed at different stages of ripening, suggesting that at least some species of chili pepper exhibit climacteric behavior [20,25].…”
Section: Chili Pepper Ripening Regulation Processmentioning
confidence: 98%
“…Metabolic changes that occur during the ripening process of chili p transformations in flavor, color, texture and aroma. Accordingly, different profiles of genes that encode key enzymes of metabolite biosynthetic pathw tinct antioxidant activity patterns during chili pepper ripening have been de early (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), breaker (36-28 DPA) and later stages (43)(44)(45)(46)(47)(48). For production of glycosides (quercetin, luteolin and apigenin) characterized th while the production of other metabolites, such as shikimic acid, putrescin butyric acid (GABA), which were highly accumulated, gradually decreased stage.…”
Section: Chili Pepper Ripening Regulation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported the presence of intra and interspecific diversity of fruit traits, metabolites content, and other agronomic traits in Capsicum species ( Ahmad et al., 2021a , 2021b ; Araceli et al., 2009 ; Chhapekar et al., 2020 ; Liu et al., 2020 ; Sarpras et al, 2016 ; Sarpras et al., 2019 ). Furthermore, many studies on marker development, QTL/gene(s) mapping of economically important traits, whole transcriptome, and genome sequencing have been reported on Capsicum species ( Ahn et al., 2014 ; Chhapekar et al., 2021 ; Dubey et al., 2019 ; Jaiswal et al., 2020 ; Kim et al., 2020 ; Liu et al., 2019 ; Martínez et al., 2021 ; Razo-Mendivil et al., 2021 ). Few studies reported that inter- and intraspecific hybrids of cultivated Capsicum species i.e.…”
Section: Introductionmentioning
confidence: 99%